The Role of Proteases in Processing of Tumour Associated Antigen(NY-ES0-1) (Journal of Pure & Applied Sciences, 2018)
The activation of T cell responses is reliant upon several steps: the uptake and processing/transforming of antigens into small peptides within specialist antigen presenting cells (APC); the binding of peptides to a class of major histocompatibility molecules (MHCs); the presentation of this complex on the surface of the APC; and the interaction of the T cell with the MHC-peptide complex. The melanoma-associated antigen (NY-ESO-1) is one of cancer testis antigens (CTAs). Because of the restricted expression of CTAs to germ cells, it has been suggested that the antigens belongs to this family could be a promising target for cancer vaccines and/or cancer immunotherapy. Therefore, their presentation to the T cells need to be elucidated for design a successful cancer vaccines. This study aims to highlight the processing of NY-ESO-1 antigen inside APC and the enzymes that are engaged in this process. The mechanisms of antigen processing of the immunogenic epitope from NY-ESO-1 antigen were studied using antigen presentation assays followed by ELISA and ELISpot, The results demonstrated that the treatment of the Dendritic cells (DCs) with the protease inhibitors affected the processing of the NY-ESO-1 protein. This indicates that the NY-ESO-1 protein requires proteolysis using proteases which are involved in the major processing (i.e., cysteine and aspartic proteases) for effective presentation to CD4 T cells. It also requires a low pH environment. In conclusion, the findings of the present study may provide further indications that, potentially, a NY-ESO1 antigen could be used in a cancer vaccine. This kind of study is at high importance for tumour immunity in terms of design tumour vaccines and modulation of tumour cells to function as antigen presenting cells and present their own antigens to the T cells.